THE PALAEOENVIRONMENTS AND DEPOSITIONAL MODEL FOR THE NGRAYONG SANDSTONES AN OUTCROP STUDY IN EASTERN PART OF THE MADURA ISLAND AS A REFERENCE - MAC. Endharto (Scientific Contributions Oil and Gas, 2006)
This topic is the most eastern portion of the se- ries depositional model of the Ngrayong Sandstone, which well develops particularly in Madura Island. This study is also observing both vertical and horizontal sequences of the sedintentological aspects and its geological associations of the Ngrayong Sandstone outcrops. The eastern part is situated between 06° 58' 10" S- 113° 46' 16" E and 06 59' 47" S- 113° 56' 09" E, that covers the eastern studies area ie, Mandala --Belukares and Prenduan to the west and Banjar Barat – Gapura - Sema to the eastern margin (Fig- ure 1). These areas are also exemplifying the east- ern most of the Ngrayong Sandstone depositional setting. Like most of the previous Ngrayong Sandstone Studies of these series is to consign the sand- stone deposition aspects especially in the main land of Madura to obtain good affiliation within the basin configuration related to hydrocarbon exploration in this region. The worked was converged on the Ngrayong Sandstone exposures to investigate the depositional style of the sandstone in the eastern portion of the island. The data mostly obtained from direct measurement of even single section of the outcrop, paleocurrent analysis and sedimentary structure, collecting the rock samples for petrographic study to see the modal analysis, di- agenesis, and reservoir characteristic.